Distribuição espacial e vertical da cigarrinha Empoasca kraemeri Ross e Moore (HEMIPTERA: CICADELIDAE) no feijão de corda. - Silva, Valeria (2012)
The objectives of this work were to study the spatial and vertical dispersion of the leafhopper Empoasca kraemeri Ross and Moore (Hemiptera: Cicadelidae), in cowpea crop [Vigna unguiculata (L.) Walp.], establish the number of samples needed to estimate the population of the pest to use in programs of Integrated Pest Management and determine the sample unit. To this task two experimental fields were cultivated in the Pici Campus in Fortaleza, Ceará. The first field had an area of 216 m², composed of 15 plots. The second field had an area of 576 m² divided into 25 plots. The cultivar used was Vita 7 with plants spaced 0.25 m x 0.8 m. We performed three separate collections of data in Field I and four in Field II on ten plants in each plot. It was counted the number of spittlebug nymphs and adults present throughout the plant. To evaluate the vertical distribution assessment was carried out at Field II on twenty-five plants, counting the number of leafhopper nymphs and adults in the first ten leaves from top to botton in its three leaflets. The results according to the aggregation indexes showed that E. kraemeri dispersion in the field follow an aggregate pattern, that was confirmed by a negative binomial frequency distribution. Thirty is the adequate number of sample unit to estimate E. kraemeri on V. unguiculata fields to be used in Integrated Pest Management programs. The ideal sites to sample E. kraemeri are 3, 4, 5 and 6 leaves. The central leaflet presents the highest number of insects.